Optimizing single-port thoracoscopic anatomical sublobar resection of the right upper lobe with computed tomography three-dimensional (3D) reconstruction technology: a retrospective cohort study - Tian, Yang; Xie, Baisheng; Song, Nannan; Wang, Jun (Frontiers in Surgery, 2025)
ObjectiveTo investigate the viability of assisting with single-port thoracoscopic anatomical sublobar resection of the right upper lobe of the lung using computed tomography three-dimensional (3D) reconstruction technology.MethodsFrom January 2021 to January 2024, 152 cases of single-port thoracoscopic anatomical sublobar excision of the right upper lobe of the lung were recorded in our hospital's Department of Thoracic Surgery. Depending on whether the 3D reconstruction technique was employed, the cases were split into two groups: one for 3D and one for 2D. The final analysis included 65 pairs (130 cases) of patients after applying 1:1 propensity score matching to compensate for baseline confounding factors. Surgical time, intraoperative blood loss, margin distance, postoperative complications, and other perioperative indicators were all statistically examined and reported.ResultsThe 3D group had significantly shorter surgical times than the 2D group (111.0 ± 19.4 vs. 142.7 ± 11.4, P < 0.001). The margin distance was significantly longer in the 3D group than in the 2D group (2.4 ± 0.4 vs. 2.1 ± 0.6, P = 0.017); Postoperative complications were significantly fewer in the 3D group than in the 2D group [7 [10.7%] vs. 16 [24.6%], P = 0.039]; The chest tube retention time was significantly shorter in the 3D group than in the 2D group (4.9 ± 1.4 vs. 5.6 ± 1.2, P = 0.005); The hospital stay was significantly shorter in the 3D group than in the 2D group (6.4 ± 1.5 vs. 7.1 ± 1.2, P = 0.005). Subgroup analysis showed that in the subgroup with the primary surgeon performing fewer than 140 procedures, the 3D group had significantly shorter surgical time and shorter hospital stay than the 2D group. In the subgroup with ≥140 surgeries performed by the primary surgeon, the 3D group had a significantly shorter surgical time, shorter hospital stay, and shorter hospital stay than the 2D group.ConclusionSingle-port thoracoscopic anatomical sublobar excision of the right upper lobe, utilizing 3D reconstruction technology, can significantly reduce surgical time, increase the surgical margin threshold, minimize hospital stays and chest tube retention times, and decrease perioperative surgical complications.